Proposed new design scheme of Vespa Club House for Vespa Club Ipoh at No.3, Jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan / Ali Imran Awang - Awang, Ali Imran (Faculty of Architecture, Planning and Surveying, 2011)
Project report is one of important subject that be taken of each student part six (06) in Diploma Interior Design or student last year in order to graduate. The objective of doing project report is to give student a foundation of understanding by broadening their knowledge of spatial design through the study of the plan and plan language This courses will make student practice to do some research based on their project proposal at part six(06). Student also should fulfill all the requirement needed and must follow the stage. This project report is about new proposal which is Proposed New Interior design scheme vespa club house at t no.3, jalan Sultan Azlan Shah, 31400 Ipoh Perak Darul Ridzuan in Malaysia. Club house is a collection information,sources,resources,and services, and the structure in which it is housed, it is housed: it is organized for use and maintained by a public body, an institution, or a private individual. In the more traditional sense, a Vespa is a collection of Vespa. The term can mean the collection, the building that houses such a collection, or both. Riders of all ages should find the club house an open, inviting, attractive, challenging and non-threatening place to visit. Vespa club house, extreme activity , entertainment and many more. In this paper we describe the meaning of club's , services, space requirement at no.3, jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan and many more. The focus is design a library that is functional, attractive children’s interests, better usual no.3, jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan in Malaysia.